PENGGUNAAN PASIR BESI SEBAGAI AGREGAT HALUS PADA BETON ASPAL LAPISAN AUS - Hamid Aly, Sumarni; Takdir, Taufik (Jurnal Transportasi, 2011)
Indonesia has the potential of natural resources of iron sand that can be used as pavement materials. Iron sand in South Sulawesi can be found in Takalar, Jeneponto, and Selayar with as many as 3.4 million tons of potential deposit. The purpose of this study is to analyze the characteristics of iron sand in a mixture of fine aggregate used as a wearing course of asphalt concrete mixtures. The characteristics of iron sand meet the specifications of asphalt concrete wearing course. The use of iron sand in the asphalt concrete mixture lowers the value of stability and increase the value of flow. The results of volumetric analysis showed that the use of sand iron reduces the voids in mixture and the voids in mineral aggregates, but increase the voids filled with bitumen. The Residual Strength Index, after immersion in water for 24 hours at a temperature of 60 Â° C, indicates that the mixture with iron sand has a lower resistance to changes in weather, temperature, and water.Key words: iron sand, asphalt concrete wearing course, Marshalls parameters.